Pengaruh Kecerdasan Emosional (EQ) dan Motivasi Belajar Terhadap Hasil Belajar Biologi Siswa Kelas XI-MIPA SMA Negeri 2 Palu - D, Mutiara; Lilies; Rafiqa; Ramadhan, Achmad; Windarsih, Yulia; Dhafir, Fatmah (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2025)
This study aims to describe the influence of emotional quotient and learning motivation on the biology learning outcomes of eleventh-grade students in the MIPA program at SMA Negeri 2 Palu. The research employs an ex post facto design that is correlational in nature, utilizing a quantitative approach. The population of the study consists of 288 students, with a sample size of 72 students selected through Cluster Random Sampling techniques. The research instruments include a student learning outcomes test, and questionnaires measuring emotional quotient and learning motivation. The results of the questionnaire tests were found to be valid and reliable. Data analysis of the questionnaire results was conducted using multiple linear regression with the assistance of SPSS version 27. The findings indicate that both variables (emotional quotient and learning motivation) have a positive and significant effect on the biology learning outcomes of the eleventh-grade students at SMA Negeri 2 Palu, both partially and simultaneously. This is evidenced by the t-test results for emotional quotient , which yielded a value of 17.514 > t-table 1.997, and for learning motivation, which yielded a value of 5.721 > t-table 1.997. Additionally, the F-test (simultaneous) produced an F-calculated value of 543.62 > F-table 3.15. Therefore, it can be concluded that there is a significant influence of emotional quetion and learning motivation on the learning outcomes of the eleventh-grade students at SMA Negeri 2 Palu.